Qualitative analysis of natural radioactive isotopes concentrations in crude oil from Saba and Al-Nasiriyah fields, Southern Iraq - Kadhim, Ali S.; Rashid, Jabbar M. (Edelweiss Applied Science and Technology, 2025)
The existence of naturally occurring radioactive materials (NORM) along with oil and gas creates a major risk to public health and the environment. Employees who have been extracting crude oil and the surrounding environment could be seriously affected if the amounts of these radioactive materials were higher than what is permitted globally. The current study was conducted to verify that the natural radioactive content of one of the fields in Thi Qar province, specifically the Saba oil field, is higher than that of the nearby fields in the same area. In this investigation, a gamma-ray spectrometry system was used based on a 3" x 3" NaI (Tl) scintillation detector to measure the natural radioactivity concentrations of 238U, 232Th, 226Ra, 228Ra, and 40K in crude oil samples taken from the Saba and al-Nasiriyah oil fields in Thi Qar province, Iraq. In the crude oil samples under examination, the highest activity concentrations of 238U, 232Th, 226Ra, 228Ra, and 40K were observed in the Saba field compared with the al-Nasiriyah field. Additionally, the maximum concentrations of the equivalent activity of 226Ra, 232Th, and 40K were also found in the Saba field. Moreover, the highest and lowest absorbed doses, which were calculated based on BECK, UNSCEAR, and ICRP, along with all other parameters such as annual effective dose (AED), the external and internal hazard indices, and lifetime cancer risks (ELCR), were identified to have maximum values in the Saba field compared to the al-Nasiriyah field. The results for every sample of crude oil showed that there were no serious radiation threats to the environment or the employees. Thus, all parameters that were measured and computed fall below the acceptable global limits recommended by the ICRP, WHO, and UNSCEAR.